Ammonium diphenylphosphinate monohydrate - Li, Dongyang (International Union of Crystallography, 2008)
In the title salt, NH(4) (+)·C(12)H(10)O(2)P(−)·H(2)O, the ion pair and water molecule interact through hydrogen bonds to form a layer structure.